(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Source of Energy is a power-producing technique that turns solar energy into electricity. It makes use of solar panels, which are frequently placed on buildings or gathered in solar farms to speed up a process that turns solar light radiation into electricity. Copper Sheet is the electrical conductor in many categories of electrical wiring. Also, the copper sheet is frequently utilized in the building and electrical appliance industries, while aluminum foil is made up of 98.5% aluminum, and the remaining 2.5% is mostly silicon and iron for strength and puncture resistance. The overall means of the electrical engineers were 3.08 with a variance of 0.044; on the other hand, the overall means of electricians were 3.21 with a variance of 0.046. The two groups of respondents obtained a T-computed value of -0.966, and the T-critical value is greater than the T-computed value, showing that there is a significant difference between the assessment of the two groups of respondents. Based on the results of the study. The t-critical value is greater than the T-computed value, showing that there is a significant difference between the assessments of the two groups of respondents.